Tratamento de efluente têxtil utilizando o processo foto-fenton - Manenti, Diego Ricieri (2011)
The aim of this work was to study the performance of the photo-Fenton process using both the artificial UV and solar sources on the textile effluent treatments. Preliminary photo-Fenton experiments for mineralization and degradation of organic and inorganic pollutants as well as of synthetic dyes were carried out in order to assess the best experimental conditions by photo-Fenton process. As synthetic textile effluent a mixture of six dyes: Solophenyl orange TGL (C25H33ClN6O6S2), Solophenyl blue 71 (C40H23N7Na4O13S4), Solophenyl scarlet BNLE (C44H32N10Na4O16S4), Solophenyl yellow ARL (C48H26N8Na6O18S6), Solophenyl black FR (C44H32N13Na3O11S3) e Navy Blue 98 (C38H24N5Na3O13S3) that contained 50 mg L-1 concentration was prepared and diluted in distillated water. The photo-Fenton experiments by using a set of high-pressure mercury lamps and solar light as artificial and natural UV irradiation sources were performed in laboratory scale. As reactor operational parameters to be optimized by a 33 full factorial experimental design: hydrogen peroxide and divalent iron ion as well as the initial solution pH were chosen as variables, keeping constant a reaction time of 120 min that was enough to warrant the maximum (chemical oxygen demand) COD and color removal. The efficiency of photo-Fenton process applied in the treatment of synthetic and real effluents, was evaluated based on the parameters: values of COD, color, turbidity, total organic carbon (TOC), absorbance at a wavelength of maximum absorption for the dyes and simple aromatic compounds and conjugated reductions, as well as behavior analysis of the evolution the sulfate, nitrate inorganic, organic nitrogen and ammonia concentrations. Second-degree models for the COD and color removal percents were proposed to model the photo-Fenton experiments data in order to reduce the cost of running such a photo-Fenton experiment as well as to obtain optimum values of the reactor operating parameters. Second-degree models were also validated by ANOVA. Predicted yields showed good validation with experimental yields. The values of the optimized reactor operational parameters were 3.0, 6.0 g L-1, and 0.05 g L-1 for initial pH, hydrogen peroxide and divalent iron concentrations, respectively, for both photo-Fenton processes. Based on this optimized experimental conditions, almost 100% removals of physico-chemical parameter such as COD, color, turbidity and COT for real textile effluents. The aromatics compounds were showed more resistant to reaction, persisting for longer. It can be noticed that the degradtion of the organic and inorganic matters were verified by the nitrification process and, the sulfates formation and reduction. The process presented similar efficiencies with both solar and artificial irradiation, thus suggesting the use of solar photo-Fenton, as it proved to be an efficient alternative besides using a source of clean and renewable energy.